1H‐Detected Solid‐State NMR Studies of Water‐Inaccessible Proteins In Vitro and In Situ. Issue 43 (27th September 2016) - Medeiros‐Silva, João; Mance, Deni; Daniëls, Mark; Jekhmane, Shehrazade; Houben, Klaartje; Baldus, Marc; Weingarth, Markus
Abstract: 1 H detection can significantly improve solid‐state NMR spectral sensitivity and thereby allows studying more complex proteins. However, the common prerequisite for 1 H detection is the introduction of exchangeable protons in otherwise deuterated proteins, which has thus far significantly hampered studies of partly water‐inaccessible proteins, such as membrane proteins. Herein, we present an approach that enables high‐resolution 1 H‐detected solid‐state NMR (ssNMR) studies of water‐inaccessible proteins, and that even works in highly complex environments such as cellular surfaces. In particular, the method was applied to study the K + channel KcsA in liposomes and in situ in native bacterial cell membranes. We used our data for a dynamic analysis, and we show that the selectivity filter, which is responsible for ion conduction and highly conserved in K + channels, undergoes pronounced molecular motion. We expect this approach to open new avenues for biomolecular ssNMR. Abstract : Within the membrane : An approach is presented that provides high‐resolution 1 H‐detected solid‐state NMR spectra of water‐inaccessible proteins, even in complex environments, such as cellular surfaces. This method was used for studying the molecular motion of the transmembrane section of an ion channel in liposomes and directly in native cell membranes.